(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
In today’s interconnected world, the efficiency of computer network addressing is more critical than ever. The exponential growth of internet-connected devices, fueled by the Internet of Things (IoT), cloud computing, and pervasive mobile connectivity, places immense strain on existing addressing schemes. This proliferation leads to rapid depletion of IPv4 addresses, increased network complexity, and potential performance bottlenecks. Inefficient addressing can result in higher operational costs, slower data transmission, and reduced network scalability, directly impacting businesses, critical infrastructure, and everyday users. Therefore, research into optimizing network addressing is not just timely but essential for the continued evolution and reliability of global digital communication.